Senecio vulgaris L. recorded as a new host plant for the root-knot nematode Meloidogyne luci - Nik SUSIČ; Saša ŠIRCA; Gregor UREK; Barbara GERIČ STARE (Acta Agriculturae Slovenica)
Meloidogyne luci is a polyphagous plant parasitic nematode species with a potential to cause great losses in agricultural production. M. luci can parasitize over thirty important crop species as well as ornamentals, herbs and weeds. In this report we documented a weed plant common groundsel (Senecio vulgaris L.) as a new naturally-infected host species which could act as a reservoir for this pest.